Cataract surgery and nonsteroidal antiinflammatory drugs. Issue 9 (September 2016) - Hoffman, Richard S.; Braga‐Mele, Rosa; Donaldson, Kendall; Emerick, Geoffrey; Henderson, Bonnie; Kahook, Malik; Mamalis, Nick; Miller, Kevin M.; Realini, Tony; Shorstein, Neal H.; Stiverson, Richard K.; Wirostko, Barbara
Abstract : N/A: Nonsteroidal antiinflammatory drugs (NSAIDs) have become an important adjunctive tool for surgeons performing routine and complicated cataract surgery. These medications have been found to reduce pain, prevent intraoperative miosis, modulate postoperative inflammation, and reduce the incidence of cystoid macular edema (CME). Whether used alone, synergistically with steroids, or for specific high‐risk eyes prone to the development of CME, the effectiveness of these medications is compelling. This review describes the potential preoperative, intraoperative, and postoperative uses of NSAIDs, including the potency, indications and treatment paradigms and adverse effects and contraindications. A thorough understanding of these issues will help surgeons maximize the therapeutic benefits of these agents and improve surgical outcomes. Financial Disclosure : Proprietary or commercial disclosures are listed after the references.